Parenting stress among parents of children with Neurodevelopmental Disorders. (30th August 2016) - Craig, Francesco; Operto, Francesca Felicia; De Giacomo, Andrea; Margari, Lucia; Frolli, Alessandro; Conson, Massimiliano; Ivagnes, Sara; Monaco, Marianna; Margari, Francesco
Abstract: In recent years, studies have shown that parents of children with Neurodevelopmental Disorders (NDDs) experience more parenting stress than parents of typically developing children, but the relation between the type of disorders and parenting stress is far from clear. The purpose of this study was to compare the parenting stress experienced by parents of 239 children with Specific Learning Disorders (SpLD), Language Disorders (LD), Autism Spectrum Disorder (ASD), Attention Deficit Hyperactivity Disorder (ADHD), and typical development (TD). Parents of children with NDDs experience more parenting stress than those of children who have TD. Although, parents of children with ASD or ADHD report the most high scores of parenting stress, also the parents of children with SpLD or LD report higher parental stress compared with parent of children without NDDs. Another interesting finding was that IQ level or emotional and behavioral problems are associated with the higher levels of parenting stress. This study suggest that parent, both mothers and fathers, of children with different type of NDDs should be provided with interventions and resources to empower them with the knowledge and skills to reduce their stress and to enhance their quality of life. Highlights: We study parenting stress of children with different Neurodevelopmental Disorders. Parents of children with ASD or ADHD report the most high scores of parenting stress. The SpLD or LD groups report higher parental stress compared with the control group. No difference in parenting stress was found between mothers and fathers. IQ level or emotional and behavioral problems are associated with parenting stress.